"i-wake device" / Farah Hanis Ariffin, Nor Ermie Md Akhaer and Muhammad Iqbal Ismail - Ariffin, Farah Hanis; Md Akhaer, Nor Ermie; Ismail, Muhammad Iqbal (2016)
i - Wake is an intelligent device that wakes brain and works by detecting when the user's eyes close while working or driving which indicates that they are fatigue and feeling sleepy. This device is built-in rechargeable system and light-weighted.